Arte, identidade e transformações na cestaria Kaingang da terra indígena Ivaí, no contexto de fricção interétnica - Santos, Tadeu dos (2018)
The objective of this study is to analyze the transformations observed in the graphic patterns, weaving, dyeing and use of different materials in the Kaingang basketwork. The methodology articulates theoretical references related to the theories of ethnicity, dialectical materialism and depth hermeneutics to investigate Kaingang Basketwork transformations, due to interethnic contact. These references are used with data collected in the field research on basketry produced by the Kaingang group of T.I.Ivaí marketed in urban centers. Theoretical references involve reflections on ethnicity, intercontinental friction and indigenous art. Field research, carried out with the Kaingang artisans, made possible the knowledge about the creation of basketry in relation to the processes of building the identity of the group in the current context of interethnic friction. The results of this study show that Kaingang handicrafts and art are transformed in the scope of artisanal production and the simple circulation of merchandise to meet human needs, and extend their aesthetic dimensions in hybridization with contemporary art. The commercialization of indigenous basketry in cities turns it into a commodity, yet it does not steal its symbolic potential as an object that expresses values of Kaingang aesthetics and culture, tied to its worldview. In conclusion the present study affirms that the phenomenon of the interethnic friction of the indigenous with the nonindigenous people in the municipality of Maringá has specificities that are manifested through an excludent mechanism that places the indigenous groups in dependence of the material resources available in the urban center.